The value of an artery clamp to dehorn cattle - Drake, C.L.; Schalles, R.R.; Smith, C.W. (Kansas State University. Agricultural Experiment Station, 2011)
A preliminary trail involving use of an artery clamp and a drawing and description of the clamp are reported in Bulletin 507. This trial involved 42 horned heifers owned and fed by a cooperating feedlot operator. The heifers were individually weighed and placed on these experimental treatments: 1. Control - not dehorned 2. Dehorned using clamp; arteries pulled 3. Dehorned not using clamp; arteries pulled All heifers were placed in one large lot and fed the same ration for 30 days after being dehorned.
Keywords: Beef; Artery clamp; Dehorning cattle; Feedlot